220k views
2 votes
Which expression is equivalent to the following complex fraction?

Which expression is equivalent to the following complex fraction?-example-1

2 Answers

1 vote

Answer:

The correct answer is last option

Explanation:

It is given that,

(1/x - 1/y)/(1/x +1/y)

To simplify (1/x - 1/y)

1/x - 1/y = (y - x)/xy

To simplify (1/x - 1/y)

1/x + 1/y = (y + x)/xy

To find equivalent expression

(1/x - 1/y)/(1/x +1/y = [(y - x)/xy]/[(y + x)/xy]

= (y - x)*xy/(y +x)*xy = (y - x)/(y + x)

Therefore the correct answer is last option

User Kamartem
by
4.6k points
4 votes

Answer: last option.

Explanation:

- Subtract the fractions that are in the numerator.

- Add the fractions that are in the denominator.

Then:


((1)/(x)-(1)/(y))/((1)/(x)+(1)/(y))=((y-x)/(xy))/((y+x)/(xy))

- Multiply the numerator of the fraction on the top by the denomianator of the fraction on the bottom.

- Simplify.

Then:


=((y-x)(xy))/((y+x)(xy))=((y-x))/((y+x))

User Dally
by
5.3k points